Transversal strength of heat-polymerized acrylic resin plate in immersion with leaf extract of basil (Ocimum basilicum L.) : Kekuatan transversa plat resin akrilik polimerisasi panas dalam perendaman ekstrak daun kemangi (Ocimum basilicum L.) - Ni Kadek Sugianitri; Suhendra; Shantika Dewi (Makassar Dental Journal PDGI Makassar, 2022)
Transverse strength is the resistance of the denture base to the load, pressure, and thrust when the mouth is functioning and is also influenced by some chemicalsas solvents, such as those contained in food, beverages and denture cleaning materials. This study was intended to determine the transverse strength of heat polymerized acrylic resin (HPAR) in a solution of basil leaf extract. The experimental design of this study was a post-test only control group with a sample size of 24 which was divided into 4 groups. Samples were soaked in sterile distilled water for 24 hours and then immersed in a solution of 25%, 50%, and 75% basil leaf extract, as well as sterile aquadest; for 8 days. The transverse strength was measured using a universal testing machine. Data were analyzed by one-way Anova and tested with least significant difference (p<0.05). The results showed that the transverse strength of the HPAR plate immersed in basil leaf extract decreased at a concentration of 25% and 50% and the lowest was at a concentration of 75%. It was concluded that basil leaf extract could decrease the transverse strength of HPAR.